RANCANG BANGUN MESIN PENGADUK ABON LELE UNTUK KELOMPOK TANI UMKM ABON LELE - Arief, Zainal; Mundari, Siti; Yuliaty, Erma (Heuristic, 2014)
Kelompok Tani Sekar Tirta a farmer group consisting of the elderly after full duty . They chosecatfish farming because it is relatively easy to handle. It turns yields less than satisfactory dueto the low selling price . Hence then think about how to keep the catfish may have added valueas well as the product can be long lasting. To begin try made it shredded catfish. It turns outthat the results are quite as demand continues to increase . This is because the product has notbeen made by other manufacturers. Next made a dry pastel catfish, catfish crackers, and piacatfish. The success of these farmer groups positive impact to the surrounding community sothat it can push some of the surrounding communities cultivate catfish also because demand forraw materials increases catfish .Along with the increasing demand Kelompok Tani Sekar Tirtaare faced with a difficulty procuring a product , to make shredded catfish takes five hours to stir. Likewise with his catfish crackers because the thickness of the product is often found to be notas well as take a long time to cut it . Through the IbM program will fix the problem because theteam managed to make IbM UNTAG Surabaya TTG mixer machine ( maker ) shredded catfish iscapable of processing 20 kg of catfish in one hour . Similarly catfish chips slicing machine TTGresults UNTAG IbM design team can also help slicing crackers catfish with the desiredthickness is uniform and in a short time .Kata kunci: Mesin mixer dan slicer, Ikan Lele, Abon Lele